2012
DOI: 10.1074/mcp.m111.014563
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Antigen-specific IgG1 Fc N-glycosylation Upon Influenza and Tetanus Vaccination

Abstract: Antibody effector functions have been shown to be influenced by the structure of the Fc N-glycans. Here we studied the changes in plasma or serum IgG Fc N-glycosylation upon vaccination of 10 Caucasian adults and 10 African children. Serum/plasma IgG was purified by affinity chromatography prior to and at two time points after vaccination. Fc N-glycosylation profiles of individual IgG subclasses were determined for both total IgG and affinity-purified anti-vaccine IgG using a recently developed fast nanoliquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
119
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 48 publications
15
119
3
Order By: Relevance
“…Statistical analyses were performed using paired t-test (comparing glycosylation-levels in first and subsequent available pregnancies) and Kruskal Wallis test (comparing subsequent pregnancies after the index pregnancy). during pregnancy and decrease after delivery (van de Geijn et al, 2009) (and this study) and is transiently increased after immunization (Selman et al, 2012a;Vestrheim et al, 2014). Interestingly, we found that anti-HPA-1a IgG1-Fc galactosylation remained high after delivery, suggesting that the antigen-specific IgG1 galactosylation is less influenced by systemic changes induced by pregnancy.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Statistical analyses were performed using paired t-test (comparing glycosylation-levels in first and subsequent available pregnancies) and Kruskal Wallis test (comparing subsequent pregnancies after the index pregnancy). during pregnancy and decrease after delivery (van de Geijn et al, 2009) (and this study) and is transiently increased after immunization (Selman et al, 2012a;Vestrheim et al, 2014). Interestingly, we found that anti-HPA-1a IgG1-Fc galactosylation remained high after delivery, suggesting that the antigen-specific IgG1 galactosylation is less influenced by systemic changes induced by pregnancy.…”
Section: Discussionsupporting
confidence: 49%
“…For example, vaccination shows transient increases in IgG galactosylation and sialylation while fucosylation is stable and remains high (Selman et al, 2012a;Bakovic et al, 2013;Vestrheim et al, 2014). The level of galactosylated IgG changes with age, disease and pregnancy (Malhotra et al, 1995;Pucic et al, 2011;Bakovic et al, 2013).…”
mentioning
confidence: 97%
“…All IgG subclasses encode an N-linked glycosylation site at residue 297 of the heavy chain. While the position of the glycosylation site is conserved, the composition and structure of the oligosaccharide added to the antibody are influenced by the host immune activation state (134,135). Variation in the antibody glycoform provides a mechanism by which antibody effector function can be fine-tuned beyond class switch recombination.…”
Section: Effector Functions Of Antibodiesmentioning
confidence: 99%
“…This discovery was made through characterization of the natural anti-HA Fc domain repertoire after seasonal vaccination in adults. It was observed that baseline levels of anti-HA IgG Fc sialylation correlated with the quality of response (affinity and hemagglutination inhibition titer) to the seasonal influenza virus vaccine [20,48]. This finding suggested a feedback mechanism for regulation of B cell selection after vaccination by sialylated ICs.…”
Section: Igg Immune Complex Immunogensmentioning
confidence: 99%